The Phonological Structure of Sundanese Language as a Representation of Regional Language Identity - Annisa Silvia; Otong setiawan Djuharie (Indo Publishing, 2026)
This research aims to describe the phonological system of the Sundanese language and analyze how the characteristics of the sound function as a pillar of identity for the speaking community. As the regional language with the second largest number of speakers in Indonesia, Sundanese has a phonetic uniqueness that clearly distinguishes it from other cognate languages. Furthermore, in an ethnolinguistic perspective, the vowel 'eu' is analyzed as a symbol of the collective identity of the Sundanese people. The results show that the use of the vowel 'eu' is not just an articulatory phenomenon, but a representation of a